Effects and New Applications of Pulsed Flow. Issue 1 (11th December 2012) - Walzel, P.
Abstract Pulsed flow has been widely applied in the past for special applications as in jigging or sorting devices, extraction columns, and fluidized‐bed dryers. Recent developments and detailed examinations demonstrate several effects which can be achieved in pulsed operation modes. Here, low‐frequency oscillations are considered, providing a more or less uniform phase state along the flow. Secondary flow is induced at obstacles and can be widely controlled by pulsation parameters keeping the backmixing effect low, despite of high transversal mass or heat exchange intensification. At walls, lift forces on particles within the thin boundary layers are beneficial for keeping particles from building deposits on surfaces or on permeable membranes. Broken symmetry devices generate a directed flow even when operated by a harmonically pulsed fluid. At oscillating interfaces, a distinct secondary flow is observed, well‐suited to intensify mass transfer.